Spatial trends in synoptic rainfall in southern Australia. Issue 14 (30th July 2013) - Risbey, James S.; Pook, Michael J.; McIntosh, Peter C.
<x xml:space="preserve">Abstract</x> [1] This work assesses spatial and temporal changes in rainfall in southern Australia over the period 1990–2009. Rainfall is assessed by season and according to the synoptic system generating the rainfall. Rainfall decreases over the period across much of the southwest, with the most significant decrease occurring around 2000. These changes are associated with frontal and cutoff systems. Frontal systems dominate the timing and changes of rainfall in western Tasmania. In the southeast, the timing and magnitude of rainfall changes are more closely associated with cutoff systems and show consistent decreases in the early 1990s. The largest reductions in rainfall in the southeast are in the Alpine region and are due to cutoffs and fronts and exhibit seasonal and spatial variations consistent with the climatologies of these systems.